TEKNOLOGI DAN DISTRIBUSI PAJAK MENDUKUNG KUALITAS PEMBANGUNAN MANUSIA - Hidayatul Prasetyowati; Jihad Lukis Panjawa (Transpublika Publisher, 2022)
The key to achieving regional development goals is the existence of human resources. This study analyzes the role of technology and tax distribution in improving the progress on human development in all provinces of Indonesia in 2015-2019.This research uses panel data regression static. In this research, there is a positive influence from technology in improving human development. These conditions indicate that the appropriate use of technology by the community can encourage the improvement of human quality resources. Other findings there is a positive influence from tax distribution in improving human development The performance of tax revenues and financing needs that are getting better and on a target in the economy can improve the quality of human development.